2021
DOI: 10.1021/acsabm.1c00130
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a Solvatochromic Optical Agent to Monitor the Polarity Changes in Dynamic Liver Injury Progression

Abstract: Unraveling the changing rule of endoplasmic reticulum (ER) polarity is of significance for liver injury. However, the rule of the ER polarity changes during the occurrence and progression of liver injury remains a mystery. Toward that, a unique fluorescent probe, ERNT, capable of imaging ER polarity in multiple liver injury models with high accuracy and fidelity was designed herein. In light of its excellent solvatochromism, the ER polarity was determined to be higher in the case of endoplasmic reticulum stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Borate is proved to be an excellent recognition site for H 2 O 2 , which can not only effectively quench the fluorescence of naphthalimide but also exhibit the advantages of rapidity, sensitivity, and high selectivity to H 2 O 2 . As for polarity detection, probes are usually constructed by D−π–A type organic fluorescent dyes with the ICT effect, which display low fluorescence intensity in strong polar medium, but weakly polar regions within cells can be imaged (membranes and lipid droplets), so compound 1 is chosen to image polarity to avoid spectral overlap with naphthalimide. Therefore, NATPA is designed and synthesized by the route shown in Scheme S1, and its structure is characterized by 1 H NMR, 13 C NMR, and HRMS (ESI).…”
Section: Resultsmentioning
confidence: 99%
“…Borate is proved to be an excellent recognition site for H 2 O 2 , which can not only effectively quench the fluorescence of naphthalimide but also exhibit the advantages of rapidity, sensitivity, and high selectivity to H 2 O 2 . As for polarity detection, probes are usually constructed by D−π–A type organic fluorescent dyes with the ICT effect, which display low fluorescence intensity in strong polar medium, but weakly polar regions within cells can be imaged (membranes and lipid droplets), so compound 1 is chosen to image polarity to avoid spectral overlap with naphthalimide. Therefore, NATPA is designed and synthesized by the route shown in Scheme S1, and its structure is characterized by 1 H NMR, 13 C NMR, and HRMS (ESI).…”
Section: Resultsmentioning
confidence: 99%
“…20), to monitor the ER polarity changes during liver injury. 115 For the first time, it was revealed that the polarity gradually increased with an increase in the severity of liver damage. Furthermore, the protective effect of the hepatoprotective drug was evaluated clearly by visualization of the polarity changes.…”
Section: Er-targeted Fluorescent Probes For Microenvironmentsmentioning
confidence: 99%
“…In 2021, Lin et al . developed a fluorescent probe ERNT for endoplasmic reticulum (ER) polarity monitor (Figure 11A) [51] . This probe can detect the polarity change in the liver damage process including fatty liver, liver fibrosis, liver cirrhosis, and liver cancer in the absence (Figure 11B) and presence of drug stimulation (Figure 11C), which are benefitable for the study in the liver tumor and environmental polarity.…”
Section: Applications Of Activatable Fluorescent Probes For Detecting...mentioning
confidence: 99%